2020
DOI: 10.3390/ijerph17113753
|View full text |Cite
|
Sign up to set email alerts
|

Willingness and Behaviors of Farmers’ Green Disposal of Pesticide Packaging Waste in Henan, China: A Perceived Value Formation Mechanism Perspective

Abstract: Environmental pollution as a result of the improper disposal of pesticide packaging wastes (PPWs) has posed serious harm to groundwater, soil and public health. However, few studies focused on PPWs green disposal willingness and behaviors of farmers from the perspective of perceived value. Based on the first-hand data, collected from 635 farmers of grain-producing counties in Henan province of China, through the questionnaire survey method, this paper adopted a structural equation model (SEM) to empirically ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…Then, the SPSS22.0 software was used to test the reliability of the total scale and each variable; the test results are shown in Table 3 . Cronbach’s α and the composite reliability value (CR value) of each variable were greater than 0.7 [ 54 ], indicating that the overall reliability of the data used in this study was good and the scale of this measurement had high reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the SPSS22.0 software was used to test the reliability of the total scale and each variable; the test results are shown in Table 3 . Cronbach’s α and the composite reliability value (CR value) of each variable were greater than 0.7 [ 54 ], indicating that the overall reliability of the data used in this study was good and the scale of this measurement had high reliability.…”
Section: Resultsmentioning
confidence: 99%
“…However, current research seldom considers the attributes of public goods in the governance of rural human settlements. Secondly, existing research finds an inconsistency between farmers’ environmental behaviour and willingness [ 63 ], and it is difficult to accurately grasp the laws of farmers’ behaviour that focuses on their willingness to participate. The administration of rural residential environment involves environmental governance, infrastructure construction, public services, toilet revolution, garbage disposal, sewage treatment, etc.…”
Section: Literature Analysismentioning
confidence: 99%
“…Specifically, the perceived benefit includes spiritual benefits in terms of environmental, physical, and mental health, reputation, and other non-material benefits; and material benefits such as gifts or subsidies provided by the local government to encourage the farmers’ WSB [ 13 , 31 ]. Studies have shown that the higher the individual’s recognition of the perceived value of waste classification, the higher the frequency of his participation in the classification [ 32 ]. Specifically, individual recognition of egoistic benefit, social-altruistic benefit, and environmental benefit has a significantly positive impact on waste classification behaviors [ 33 , 34 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%